Using virtual reality (VR) for teaching and learning in geography: fieldwork, analytical skills, and employability. Issue 3 (3rd July 2022) - Bos, Daniel; Miller, Servel; Bull, Eloise
ABSTRACT: This article outlines how Virtual Reality (VR) technologies, software and content can be used as a resource for teaching and learning in Geography. Drawing on the authors' first-hand experiences of using VR for undergraduate and postgraduate teaching, we explore firstly how VR can enhance the development of fieldwork observational techniques, knowledge and understanding of place, prior to entering the field. Secondly, we show how VR can be used to enable students to develop critical analytical skills in relation to emergent visual technologies and the wider implications VR has for the representation of people, places and landscapes. Finally, the article will attend to the ways VR and Augmented Reality (AR) – due to its growing industrial application – can offer important opportunities for the development of unique practical employability skills which can be applied to the geovisualization of data and environments enhancing graduate career prospects.